SARAJEVO – ZAGREB – CRACOW. ON DESERTED, DISCARDED AND REFOUND PLACES ON THE AUSTRO-HUNGARIAN MAP OF IVO ANDRIĆ’S BIOGRAPHY - Nowak-Bajcar, Sylwia (Porównania, 2012)
At the beginning of April 1914 Ivo Andrić, the young poet, after completing college education in Sarajevo (1911), and than after brief episodes of studies in Zagreb (1912) and Vienna (1913), decided to undertake studies at the Jagiellonian Univesity in Cracow. Why did conventional bourgeois world, at first glance not so different from world of salons in Zagreb and Vienna, seem to be a “better world” for the writer of Croatian-Bosnian roots? Presenting Andrić’s choices on the eve of World War I, reflected in his gestures of rejection, as well as gestures of afimation, I show the role of meeting with Cracow and the Polish culture in formation of his hybrid Yugoslavic identity. Documentaries are the starting point for reflection on the influence of the genius loci of Cracow on the formation of the intellectual silhouette of the Yugoslavic Nobel-Prize winner (1892–1975).